تقييم نقص الكلمة من خالل اقتراح برنامج معلوماتي عن طريق تسمية وتعيين الصور عند المصابين بمرض الزهايمر - جبار, نسرين صبيحة (كلية العلوم الاجتماعية, 2025)
تهدف هذه الدراسة إلى بناء برنامج معلوماتي متخصص لقياس ظاهرة نقص الكلمة لدى مرضى الزهايمر، باعتبارها من أبرز الاضطرابات اللغوية التي تظهر في المراحل المبكرة من المرض. وتكمن أهمية الدراسة في الحاجة إلى أدوات رقمية دقيقة تسهم في التشخيص المبكر ومتابعة التدهور اللغوي.حيث اعتمدت الدراسة على المنهج التطويري التطبيقي، وتم تصميم برنامج يحتوي على فقرات مصورة، تشمل مهاما مثل: تسمية الصور وتعيينها،لقياس قدرة المرضى على استرجاع الكلمات واستخدامها.طبق البرنامج على عينة مكونة من 30 شخصا سليما للتحقق من صدق الأداة وثباتها. وأظهرت النتائج ان معامل الفا كرونباخ بلغ (0.90) في بند التعيين و (0.89) في بند التسمية، ما يدل على اتساق داخلي مرتفع.كما أشار معامل ارتباط برسون بين التطبيقين الأول والثاني الى (0.85) لبند التعيين و (0.93) لبند التسمية.وتمثلت العينة المرضية في 5 حالات مشخصة بالزهايمر بدرجات متفاوتة، تم تأكيدها باختبار MMSE.أظهرت النتائج وجود ضعف ملحوظ في أداء المرضى في المهام التي تتطلب استرجاعا حرا، مع تحسن الأداءعند وجود تلميحات. كما ساه البرنامج في رصد الاضطراب بدقة وسرعة. توصي الدراسة باعتماد مثل هذه البرامج المعلوماتية في المؤسسات الصحية كوسيلة فعالة لمتابعة التدهور اللغوي لدى مرضى الزهايمر. This studyaims to develop a specializedinformational program to measure the phenomenon of word-findingdifficulties in Alzheimer's patients, as itis one of the mostprominentlinguisticdisordersthatappear in the early stages of the disease. The importance of the study lies in the need for precise digital toolsthatcontribute to earlydiagnosis and monitoring of linguisticdeterioration. The studyrelied on the developmental-appliedapproach, and a program wasdesignedcontainingvisual items, includingtaskssuch as naming and assigningpictures, to measure the patients' ability to retrieve and use words. The program wasapplied to a sampleconsisting of 30 healthyindividuals to verify the validity and reliability of the tool. The resultsshowedthat the Cronbach's alpha coefficient was (0.90) for the assignment item and (0.89) for the naming item, indicating high internalconsistency. The Pearson correlation coefficient between the first and second applications indicated (0.85) for the naming item and (0.93) for the labeling item. The patient sampleconsisted of 5 cases diagnosedwithAlzheimer's at varyingdegrees, confirmed by the MMSE test. The resultsshowed a significantimpairment in the patients' performance in tasksrequiring free recall, withimproved performance when prompts wereprovided. The program alsocontributed to accurately and quicklydetecting the disorder. The studyrecommendsadoptingsuchinformational programs in healthcare institutions as an effective means to monitor languagedeterioration in Alzheimer's patients.
Keywords: المعجم الذهني, الوصول المعجمي,استحضار الكلمة, مرض الزهايمر